STRATEGI PENGUATAN KAMPUNG GLINTUNG GO GREEN (3G) SEBAGAI DESTINATION BRANDING OBYEK WISATA EDUKASI DI MALANG - Ima Hidayati Utami (Adbis: Jurnal Administrasi dan Bisnis, 2017)
This study aimed to strengthen Kampung Glintung Go Green (3G) as a brand destination of an educational tourism object in Malang – East Java. Employing a qualitative approach,the primary data were collectedthrough in-depth interview, observasion, and FGD with Community Unit (RW) managements,Neighborhood Unit (RT) managements, and 3G management. While the secondary data were collected fromrelated documents. The research findings showed that Kampung Glintung residents have developed 3Gmanagement to manage kampung educational tourism ; created short-term roadmap in three years; formulated vision and mission; anddeveloped an education tourism destination brand. Yet, thefindings indicated that the brand destination they created needed to be reinforced to get more visitors. Therefore, the researcher workedtogether with 3G management and residents representatives carried out the following steps: (1) reformulating brand elements by designing new vision and mission, developing brand essence and brand image; (2) designing new logo based on conceptsproposed by thecommunity ; (3) creating tagline based on the proposed concept; (4) developing an alternative campaign media using video profile and internet-based media.